Distal Biceps Tendon Repair Using A Single-incision Approach With Unicortical Intramedullary Button Fixation: Report Early Post-operative Outcomes And Complications. Issue 7 (29th July 2019) - Lin, Kenneth M.; Chan, Justin; Lin, Brian J.; Camp, Christopher L.; Garcia, Grant Hoerig; Taylor, Samuel A.; Cordasco, Frank A.; Dines, Joshua S.
Objectives: While various techniques for distal biceps repair have been described, biomechanical studies have shown cortical button fixation to outperform bone tunnels, intraosseous screws, and suture anchors. Furthermore, numerous studies have shown no difference in complication rate between single- and dual-incision approaches. Thus, it follows that a single-incision approach with cortical button fixation may provide superior clinical outcomes with minimal complications. The purpose of this study is first to investigate intra-operative and short-term complications of distal biceps tendon repair through a single-incision approach using unicortical button fixation, and secondly to assess clinical outcomes. Methods: 52 patients who underwent distal biceps repair with unicortical button fixation (Figure 1) at a single institution from 2014 to 2017 were identified. Exclusion criteria included age less than 18 or greater than 75 years, prior ipsilateral biceps repair, concomitant ipsilateral surgical procedure, and most recent follow-up less than 2 months. Postoperative nerve deficits, flexion and supination strength by manual testing, range of motion, Mayo Elbow Performance Score (MEPS) and radiographs for identification of heterotopic ossification (HO) were obtained and analyzed retrospectively. Results: Fifty-two patients with 53 distal biceps ruptures were included, with mean age 48 years (range 25-71 years). Median time from injury to surgery was 2 weeks (range 1 day to 16 weeks), with 15 patients being treated at greater than 3 weeks from injury. Forty-four patients (83%) had complete tears. Following surgery, average time to final follow-up was 22.8 weeks (range 8-65 weeks). Postoperatively, 49 patients (92.5%) had full range of motion, 48 patients (90.6%) had return of full supination and flexion strength by manual muscle testing (the remaining patients had strength graded as 5-/5). There was no difference in outcomes between those patients treated < 3 weeks from injury compared to those treated > 3 weeks from injury. Two patients (3.8%) initially reported sensory deficit in the lateral antebrachial cutaneous nerve distribution, both cases of which fully resolved by 7 and 11 weeks postoperative. Two patients (3.8%) displayed radiographic evidence of heterotopic ossification, Hastings and Graham class I (Figure 2). One of these was an incidental finding without any clinical symptoms, the other had mild pain but normal strength and neurovascular function. Mean postoperative MEPS was 93.9 (range 60-100), corresponding to "excellent" function (MEPS>90). Conclusion: Distal biceps repair using single incision, unicortical button fixation yields a low rate of complications with good clinical results compared to other techniques reported in the literature. The single incision approach in patients treated between 3 and 16 weeks from injury is safe and resulted in outcomes no different than in those patients treated <3 weeks from injury. Further investigation is warranted in the form of larger, comparative studies with more robust outcome measures and longer term follow up. Figure 1. Demonstrative radiograph showing unicortical, intramedullary placement of tenodesis button . The button is inside the medullary canal and engaging the near cortex. Intraoperatively, button position can be confirmed using fluoroscopy. Figure 2. Postoperative heterotopic ossification, Hastings and Graham class I, seen on lateral elbow radiograph in 2 patients . A: radiograph taken at 6 weeks post-op; prior radiograph from 2 weeks post-op showed no evidence of ectopic bone formation. B: radiograph taken at 1 year post-op in a different patient; prior radiograph from 2 weeks post-op did not demonstrate any focus of ectopic ossification in anterior soft tissues. Both radiographs were taken as part of routine surgeon follow-up protocol. The patient in frame A was completely asymptomatic, while the patient in frame B had mild pain at extremes of motion but full range of motion and strength.